The influence of light wavelength and intensity to the survival rates, growth rates and production index of Sutchi Catfish larvae - Ismail, Khairul Muttaqin; Rosli, Khairul Anwar; Tan, Nai Han; Mohammad Noor, Normawaty; Mukai, Yukinori (2019)
Sutchi catfish Pangasianodon hypophthalmus (Sauvage, 1878) is one of the most important freshwater fish species cultured in Southeast Asia. Artificial seed production of sutchi catfish is very important in aquaculture industry. However, the larval survival rates were low when reared in the hatchery. Providing optimum rearing condition for sutchi catfish larvae in the hatchery can increase the seeds production. Light conditions was reported to influence the survival and growth of fish. Hence, this study was conducted to examine the optimum light conditions in term of light wavelength and light intensity for rearing of sutchi catfish larvae. The sutchi catfish larvae were reared under five different light wavelengths (white, blue, green, yellow and red lights) and four different light intensities (1.40 10-4 , 1.40 10-3 , 1.40 10-2 , and 1.40 10-1 µmol/m²/s). The results showed that, the survival rates (SR), growth rates (SGRTL and SGRBW) and Production Index (PI) were higher in red light than other wavelengths. For light intensity, only PImshown significant effect to the larvae. Light intensity of 1.40×10-3 µmoles/m²/s wasmsignificantly higher than 1.40×10-1 µmoles/m²/s intensity. Apart from that, there weremtendency for high SR, SGRTL and SGRBW under low light intensities (1.40 10-4m and 1.40 10-3 µmoles/m²/s) when compared to high light intensities (1.40 10-2, and 1.40 10-1 µmol/m²/s). Therefore, red light wavelength and low light intensities (1.40 10- 4 and 1.40 10-3 µmoles/m²/s) were recommended when rearing sutchi catfish larvae.